Situation Report: Hungary, 6 February 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Consumers Hit by Still More Steep Price Increases / by Alfred Reisch Deficiencies in the System of Economic Regulators Yugoslav Journalist Praises Hungary's Agricultural "Miracle" / by Slobodan Stankovic Hungarian Jewish Leaders Rebuked for Signing Anti-American Statement / by Alfred Reisch When a Tip Becomes a Bribe / by Eva Lengyel Western Praise Puts Hungary in Difficult Position, Yugoslav Claims / by Slobodan Stankovic Growing Interest in Religion and the Churches among Hungarian Youth / by Alfred Reisch